Design of Lubricating Oil Circulation Refrigeration System for Cigarette Machine - Zhou, Bo; Yang, Jing; Wang, Xiang; Chen, Sixiao; Hu, Linsong; Wu, Kaiyang (Transactions on Engineering and Technology Research, 2023)
In order to solve the problems of high lubricating oil temperature, fast aging of seals and serious wear of parts during high-speed operation of equipment, a lubricating oil circulation refrigeration system for cigarette machine was designed. The system uses PLC as the main controller, and controls the motor speed through Profibus bus mode to realize the circulating refrigeration of lubricating oil. Through the test with ZJ112 unit as the object,we found that the system runs well and the failure rate is low. The temperature of each lubricating part of the equipment is significantly reduced and kept below 40 ˚C. At the same time, the maintenance time of the equipment is reduced, and the occurrence of cigarette quality accidents is reduced. This technology can provide support for improving the production adaptability of cigarette units.